2022
DOI: 10.3390/jmse10050681
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Commercial-Scale Seaweed Cultivation on Water Quality: A Case Study in a Typical Laver Culture Area of the Yellow Sea, North China

Abstract: Seaweeds are important to marine ecosystems through biogeochemical processes. Laver are the most widely farmed seaweeds with the largest culture area in China. This study analyzes the water quality characteristics in a large-scale laver culture area (Taoluo) by comparing a small-scale laver culture area and non-culture areas, thereby assessing the changes in water quality due to large-scale laver cultivation. Particulate organic carbon and/or dissolved organic carbon decreased while the total suspended solid i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 49 publications
1
4
0
1
Order By: Relevance
“…Es importante tener en cuenta estos rangos dentro de los parámetros ambientales, ya que como lo visto en la revisión si se mantienen puede dar tasas de crecimiento favorables para las distintas especies de macroalgas rojas. Por ejemplo, la temperatura del mar es uno de los parámetros frecuentemente considerados, ya que es susceptible y variable conforme a las condiciones hidrológicas (lluvia y evaporación) y meteorológicas (temperatura del aire, radiación, velocidad del viento y corriente), asimismo la salinidad que varía conforme a las estaciones y el lugar donde se evalúa, el pH varía por el ingreso de tierra al medio acuático; por ello, el cultivo de macroalgas rojas es un gran regulador del pH y el OD por las capacidad de fijación de carbono y evolución fotosintética de oxígeno que estas presentan [34]. Además, de acuerdo a la especie de macroalga roja cultivada, esta se puede ver influenciada relevantemente por la temperatura del agua, la salinidad, el pH y los nutrientes (amoníaco, nitrato y fosfato) presentes en el medio; caso contrario se observarán alteraciones en el crecimiento y características de la especie [39].…”
Section: Resultados Y Discusiónunclassified
“…Es importante tener en cuenta estos rangos dentro de los parámetros ambientales, ya que como lo visto en la revisión si se mantienen puede dar tasas de crecimiento favorables para las distintas especies de macroalgas rojas. Por ejemplo, la temperatura del mar es uno de los parámetros frecuentemente considerados, ya que es susceptible y variable conforme a las condiciones hidrológicas (lluvia y evaporación) y meteorológicas (temperatura del aire, radiación, velocidad del viento y corriente), asimismo la salinidad que varía conforme a las estaciones y el lugar donde se evalúa, el pH varía por el ingreso de tierra al medio acuático; por ello, el cultivo de macroalgas rojas es un gran regulador del pH y el OD por las capacidad de fijación de carbono y evolución fotosintética de oxígeno que estas presentan [34]. Además, de acuerdo a la especie de macroalga roja cultivada, esta se puede ver influenciada relevantemente por la temperatura del agua, la salinidad, el pH y los nutrientes (amoníaco, nitrato y fosfato) presentes en el medio; caso contrario se observarán alteraciones en el crecimiento y características de la especie [39].…”
Section: Resultados Y Discusiónunclassified
“…Waves and winds influence the movement of currents, stirring up bottom sediments, and increasing the turbidity. Meanwhile, water turbidity is closely related to cloudiness caused by the abundance of organic and mineral particles such as sand, microorganisms, decaying plants, and animals, as well as human waste discharge (Liang et al 2022). Murky waters also obstruct the penetration of sunlight, hindering optimal photosynthesis in seaweed.…”
Section: Identification Of Bacteria Causing Ice-ice Disease In Seaweedmentioning
confidence: 99%
“…Climate change has been predicted to result in elevated seawater temperatures, declining salinity (caused by increases in rainfall), coastal eutrophication and ocean acidification. The correlations between large-scale seaweed cultivation and the change of some environmental factors have been discussed [46][47][48], and previous studies have reported the relationships between wild macroalgal communities and abiotic factors [49][50][51][52]. They found that macroalgal abundance, distribution, and diversity responded to variability in salinity, light availability, nutrient availability, depth, bottom type, and wave exposure, and that the tissue-nutrient content in macroalgae was variable in space and time.…”
Section: The Influence Of Ecological Factors On the Contents Of Nutri...mentioning
confidence: 99%